2017
DOI: 10.1016/j.ab.2016.10.024
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic and kinetic approaches for evaluation of monoclonal antibody - Lipoprotein interactions

Abstract: Two complementary instrumental techniques were used, and the data generated was processed with advanced numerical tools to investigate the interactions between anti-human apoB-100 monoclonal antibody (anti-apoB-100 Mab) and apoB-100 containing lipoproteins. Partial Filling Affinity Capillary Electrophoresis (PF-ACE) combined with Adsorption Energy Distribution (AED) calculations provided information on the heterogeneity of the interactions without any a priori model assumptions. The AED calculations evidenced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 24 publications
1
19
0
Order By: Relevance
“… 86 Partial filling (PF) ACE was combined with adsorption energy distribution to determine the heterogeneity of interaction of apoB-100 containing lipoproteins and their antibodies. 87 The interaction proved homogeneous and PF-ACE results were in alignment with quartz crystal microbalance experiments.…”
Section: Applicationssupporting
confidence: 66%
“… 86 Partial filling (PF) ACE was combined with adsorption energy distribution to determine the heterogeneity of interaction of apoB-100 containing lipoproteins and their antibodies. 87 The interaction proved homogeneous and PF-ACE results were in alignment with quartz crystal microbalance experiments.…”
Section: Applicationssupporting
confidence: 66%
“…These lipoproteins are actually mixtures of various proportions of esterified and nonesterified cholesterol, phospholipids, proteins, triglycerides, and surface apolipoproteins [ 8 ]. Kinetic studies have identified a lot of variability in terms of shape, size, and lipid composition which are difficult to measure as perfection in clinical laboratories provided improvement in laboratory science and calibration practices [ 9 ]. The recent data has subcategorized LDL particles based upon their size and density into small and dense LDL-cholesterol particles termed small density LDLc (sdLDLc) and large dense LDL-cholesterol, which has been proven to be more predictive to highlight underlying cardiovascular risks [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“… 1 However, for detailed characterizations of interactions between more complicated and larger biomolecules, for example, biological drugs and their target receptors in biochemical assays, more advanced data analysis approaches are crucial. 3 5 These approaches should not be considered a replacement for carefully executed experiments but as a way to deal with situations where more complicated interactions are present.…”
mentioning
confidence: 99%